Efektivitas Serapan Jagung Lokal Oleh Pabrik Pakan di Indonesia - Ibnu Dwi Santoso; Puguh, Susilo (CV. Komunitas Dunia Peternakan, 2024)
The uptake of local corn by feed factories nationally in corn production and demand between regions is uneven, which creates corn shortages, so information services are needed for business actors. This research aims to analyze the effectiveness of local corn uptake by feed factories nationally using descriptive qualitative methods. The results of the research show that the local corn uptake information service in the Sijagung application from the five dimensions of Campbell's service effectiveness, namely service success, target success, satisfaction with service, level of input and output and achievement of overall goals is considered less effective because there is no updated data information, does not provide information projection data as corn absorption data required by feed factories nationally. To achieve the effectiveness of corn uptake information services by feed factories through the Sijagung application, it needs to be strengthened with a service integration dimension used to measure the extent to which the presentation of local corn uptake data nationally can be integrated with harvest condition data so that it can display projection data for Business Actors in making decisions to carry out purchase.